Remote control system for energy efficient home - Guangxi Wu; Xiong Yu (2013 IEEE Energytech, 2013)
This paper introduces the development of an innovative remote home appliances control system for applications in energy efficient smart homes. The system parses its control command based on email interfaces. The paper firstly provides an overview of the system and the major components. It describes the e-mail command protocols, power line communication protocol, as well as the remote control algorithms used in the system. A pilot system has been successfully implemented. The results of testing indicate the remote control system is reliable and fast responsive. It provides an important control for reduce energy consumption in buildings. Aspects of the system that can be further improved are discussed.